When healers get wounded! Moral injury in healthcare providers during the COVID-19 pandemic in Pakistan - Fatima, Madah; Imran, Nazish; Aamer, Irum; Iqtadar, Somia; Shabbir, Bilquis (Frontiers in Psychiatry, 2023)
Moral injury is a multi-faceted and multidimensional phenomenon. Occupational moral injury has been studied mainly among military personnel and first responders and is linked to mental health problems. Moral Injury encompasses negative moral emotions such as shame, guilt, and anger leading to distress, and impairment in social and occupational functioning. The COVID-19 pandemic predisposed healthcare providers to moral dilemmas, Potentially Morally Injurious Events (PMIEs), and moral injury. We aimed to assess the prevalence and predictors of moral injury in healthcare providers during the COVID-19 pandemic in Pakistan. This cross-sectional study was conducted in July-October 2021 among physician/clinician staff working at teaching hospitals in Lahore. The Moral Injury Symptoms Scale-Health Professionals (MISS-HP) was used to collect data. SPSS 26 was used for data analysis applying Wilcoxon Mann-Whitney U and Kruskal Wallis tests on non-normally distributed data at α=0.05. Predictors of moral injury were ascertained through Binary Logistic Regression analysis. Results: 420 physicians responded to the questionnaires. The median (IQR) moral injury scores were 37(28-47). Guilt, moral concerns, and shame were higher-scoring moral injury dimensions. 40.8% (n=171) suffered from clinically significant distress and impaired functioning while 14.3% (n=60) from severe distress. Gender, department, and history of psychiatric illness predicted higher levels of distress which were 1.9 times higher in females than males and 2.5 times higher with a history of psychiatric illness. Working on the front lines did not predict moral injury. Conclusions: Our findings highlight the substantial burden of moral injury in our sample during COVID-19, having implications for healthcare providers' well-being, healthcare quality, and service delivery. This calls for concerted efforts from all stakeholders to better prepare for future disasters through effective human-resource policies, pre-trauma exposure soft-skills training, effective teamwork and communication strategies; self-stewardship and resilience modules, and mental health support for healthcare providers. The dimensional construct of moral injury may vary across cultures; hence we recommend further cross-cultural research on moral injury in healthcare providers, particularly in the context of public health disasters.